2010
DOI: 10.1095/biolreprod.109.082321
|View full text |Cite
|
Sign up to set email alerts
|

Differential Endometrial Gene Expression in Pregnant and Nonpregnant Sows1

Abstract: In an attempt to unveil molecular processes controlling the porcine placentation, we have investigated the pregnancy-induced gene expression in the endometrium using the Affymetrix GeneChip Porcine Genome Array. At Day 14 after insemination, at the time of initial placentation, samples were obtained from the endometrium of pregnant sows and sows inseminated with inactivated semen. Analysis of the microarray data revealed 263 genes to be significantly differentially expressed between the pregnant and nonpregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 53 publications
6
58
0
Order By: Relevance
“…Although LIFR mRNA was previously demonstrated to be expressed in the porcine endometrium on Days 11,18,30, and 60 of gestation [4], our results are the first to compare the profiles of LIFR expression in cyclic and pregnant gilts on the corresponding days after estrus. Profile of endometrial expression of LIFR mRNA on Day 14 of pregnancy vs. the estrous cycle is in agreement with the results of the recently performed microarray analysis of the endometrial transcriptomes [14]. The increased expression of the LIF and LIFR in the porcine endometrium on Days 12-16 of pregnancy (present data) coincides with elevated LIF content in the uterine lumen (Day 12) and abundant expression of LIFR mRNA in the porcine conceptuses (Day 14) [3], which confirms the important role of this system during maternal recognition of pregnancy and implantation.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Although LIFR mRNA was previously demonstrated to be expressed in the porcine endometrium on Days 11,18,30, and 60 of gestation [4], our results are the first to compare the profiles of LIFR expression in cyclic and pregnant gilts on the corresponding days after estrus. Profile of endometrial expression of LIFR mRNA on Day 14 of pregnancy vs. the estrous cycle is in agreement with the results of the recently performed microarray analysis of the endometrial transcriptomes [14]. The increased expression of the LIF and LIFR in the porcine endometrium on Days 12-16 of pregnancy (present data) coincides with elevated LIF content in the uterine lumen (Day 12) and abundant expression of LIFR mRNA in the porcine conceptuses (Day 14) [3], which confirms the important role of this system during maternal recognition of pregnancy and implantation.…”
Section: Resultssupporting
confidence: 89%
“…The present results are the first to compare the pattern of IL6R mRNA expression in the porcine endometrium during the estrous cycle and early pregnancy. Recent report showed a similar expression pattern of IL6R mRNA in the endometrium of pregnant animals on Day 14 [14]. The increased IL6 protein content in endometrium of pregnant animals [3] and upregulated expression of IL6R in the endometrium on Day 14 of pregnancy (the current study) and conceptuses (Days 10-12) [3] suggest that IL6 is substantial component of embryo-maternal crosstalk required for successful implantation.…”
Section: Resultssupporting
confidence: 79%
“…These efforts, along with global gene expression studies, have tremendously advanced our understanding of porcine pregnancy and endometrial biology. In recent years, while many global gene expression studies in the porcine endometrium have been conducted on differential gene expression during pregnancy [11][12][13][14], there are very few reports regarding global changes in porcine endometrial proteome during pregnancy [6,15]. Kayser et al [6] reported changes in uterine fluid proteome during early porcine pregnancy and some proteins reported by them are common to this study.…”
mentioning
confidence: 57%
“…ALDR (or AKR1B1) levels changed only with the progression of pregnancy with a~9-fold increase in Day 12 versus Day 9. The AKR1B1 gene has previously been shown to have a specific expression on Days 12 and 13 of porcine pregnancy [12,65]. Besides countering oxidative stress [66], in endometrium members of the aldo-keto reductase family, including ALDR, play an important role in the biosynthesis of prostaglandins [13,67], participating in pregnancy recognition and conceptus development in pigs [68].…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate endometrial responses at the level of gene expression, or more specifically, changes in mRNA concentrations, several microarray and RNA-seq studies have been performed for Day 12 as the time of MRP (57) and for Day 14 (58,59) and as the time of beginning of conceptus implantation. Particularly in the RNA-seq studies, a plethora of transcriptome changes in porcine endometrium during the preimplantation period were observed.…”
Section: Transcriptome Studies Of Porcine Endometrium During the Preimentioning
confidence: 99%